PENGUATAN MODERASI BERAGAMA BERBASIS KEBANGSAAN PADA SISWA REMAJA DI MASJID AL-MA’HAD DUKUPUNTANG - Theguh Saumantri; Jefik Zulfikar Hafizd; Riza Fasya Faturrakhman (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Religion and nationality have a central role in shaping the identity and character of a nation. In Indonesia, which is a country with ethnic, religious, and cultural diversity, understanding religious moderation and national values is the main foundation for social harmony and state sustainability. Mosques, as religious institutions and centers of community activities, have great potential to strengthen the understanding of religious moderation and national values in the younger generation. This article aims to describe the community service program carried out for teenagers at the Al-Ma'had mosque in Cirebon Regency. In this community service, participatory action research (PAR) methodology is used as a strategy to achieve the goals of service. This method is a form of knowledge production instrument that involves active participation from the community in every stage of service, from planning, and implementation, to evaluation. The service results explain that this program creates higher awareness among teenage students about their role in building a more harmonious and peaceful society and contributes to the formation of a generation that is more tolerant, harmonious, and loves the country.